Milk production, nitrogen utilization, and methane emissions of dairy cows grazing grass, forb, and legume-based pastures. (16th July 2020) - Wilson, Randi L; Bionaz, Massimo; MacAdam, Jennifer W; Beauchemin, Karen A; Naumann, Harley D; Ates, Serkan
Abstract: Achieving high animal productivity without degrading the environment is the primary target in pasture-based dairy farming. This study investigated the effects of changing the forage base in spring from grass-clover pastures to forb or legume-based pastures on milk yield, N utilization, and methane emissions of Jersey cows in Western Oregon. Twenty-seven mid-lactation dairy cows were randomly assigned to one of three pasture treatments: grass-clover-based pasture composed of festulolium, tall fescue, orchardgrass, and white clover (Grass ); forb-based pasture composed of chicory, plantain, and white clover (Forb ); and legume-based pasture composed of red clover, bird's-foot trefoil, berseem clover, and balansa clover (Legume ). Pastures were arranged in a randomized complete block design with three replicates (i.e., blocks) with each replicate grazed by a group of three cows. Production and nutritive quality of the forages, animal performance, milk components, nitrogen partitioning, and methane emissions were measured. Feed quality and dry matter intake (DMI ) of cows were greater ( P ≤ 0.05) for Legume and Forb vs. Grass, with consequent greater milk and milk solids yields ( P < 0.01). Cows grazing Forb also had more ( P < 0.01) lactose and linoleic acid in milk compared with cows grazing the other pastures, and less ( P = 0.04) somatic cell counts compared with Grass. Cows grazing Forb had substantially less ( P < 0.01) N in urine, milk, and blood compared with cows grazing the other pastures, with not only a greater ( P < 0.01) efficiency of N utilization for milk synthesis calculated using milk urea nitrogen but also a larger ( P < 0.01) fecal N content, indicating a shift of N from urine to feces. Both Forb and Legume had a diuretic effect on cows, as indicated by the lower ( P < 0.01) creatinine concentration in urine compared with Grass. Methane emissions tended to be less ( P = 0.07) in cows grazed on Forb vs. the other pastures. The results indicate that Forb pasture can support animal performance, milk quality, and health comparable to Legume pasture; however, Forb pasture provides the additional benefit of reduced environmental impact of pasture-based dairy production.